Androgen Receptor (AR), E-Cadherin, and Ki-67 as Emerging Targets and Novel Prognostic Markers in Triple-Negative Breast Cancer (TNBC) Patients - Ricciardi, Giuseppina Rosaria Rita (PLoS One, 2015)
BACKGROUND: TNBC is an aggressive subset of breast cancer (BC) without specific target therapy. METHODS: This observational, retrospective study included 45 cases of TNBC. The aim of this study was to evaluate the expression of the AR, E-cadherin and Ki-67 in relation to histological type, time to relapse and overall survival (OS). Immunohistochemistry (IHC) was carried out on formalin-fixed paraffin-embedded tumor samples obtained from patients defined TNBC. RESULTS: The AR was positive (IHC >10%) in 26.6%. E-cadherin (CDH1) expression was considered positive if the score was ≥ 2. This expression was negative in 53.3% cases. The Ki-67 index was ≥ 20% in 37.7%. Univariate analyses showed that AR, CDH1 and Ki-67 are significantly associated with OS. Multivariate analysis showed that AR and Ki-67 expression are independent variables associated with OS. The statistical analysis showed that patients with AR negative and Ki-67 positive expression have a significant correlation with poor outcome. CONCLUSIONS: Our data suggest that the combination of AR and E-cadherin expression as well as Ki-67 status might be useful prognostic markers in TNBC. Hence, these molecular determinants could play an interesting role to classify subgroups of TNBC.